Dive efficiency versus depth in foraging emperor penguins - Rory Wilson (Aquatic Biology, 2010)
Zimmer, I., Wilson, R.P., Beaulieu, M., Ropert-Coudert, Y., Kato, A., Ancel, A., Plötz, J. 2010). Dive efficiency versus depth in foraging emperor penguins. Aq. Biol. 8; 269-277.